(untitled) (Homoeopathy for All, 2024)
Standardisation is defined as an activity that gives rise to solutions for repetitive use of the activity. Generally, the activity constitutes the process of establishing and implementing standards. Thus, SOPs (Standard Operating Procedures) are the perfect result of a standardisation activity. High levels of quality are important to accomplish manufacturer’s business objective. SOP is a back bone of any pharmaceutical industry, having a deep symbiotic relationship between compliance and quality. SOPs are intended to be specific to the organisation or a particular facility. A well written SOP reflects the image of the company. The current article focuses mainly on the definition of SOP, its significance and benefits, types of SOPs, writing style, formats of SOP and its use.